2020
DOI: 10.24071/jpsc.001698
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant And Anticancer Activities Of Murbei (Morus Alba L.) Stem Extract On In Vitro WiDr Cancer Cells

Abstract: Mulberry is considered as an important plant in traditional Chinese medicine, due to its various compounds, including phenols and flavonoids. These flavonoids have antioxidant activities so that can be a potential anticancer candidate. The aims of this study were to determining antioxidant activity, phenolic content, and potential anticancer activity in Mulberry stem extract. The extraction was carried out by maceration using ethanol as the solvent, antioxidant activity test using ABTS (2,2′-azinobis-(3-ethylb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Many bioactive compounds have shown specific role as anti-cancer agents. The presence of polyphenolic compounds 30,31 , tannins 32 , anthraquinone glycosides 33 , cardiac glycosides 34 and terpenoids 35 which specifically are known to possess anticancer properties makes MI hybrid varieties a novel source of nutraceutical compounds. Though certain compounds are present in smaller amounts, they work synergistically and exhibit their biological role.…”
Section: Discussionmentioning
confidence: 99%
“…Many bioactive compounds have shown specific role as anti-cancer agents. The presence of polyphenolic compounds 30,31 , tannins 32 , anthraquinone glycosides 33 , cardiac glycosides 34 and terpenoids 35 which specifically are known to possess anticancer properties makes MI hybrid varieties a novel source of nutraceutical compounds. Though certain compounds are present in smaller amounts, they work synergistically and exhibit their biological role.…”
Section: Discussionmentioning
confidence: 99%
“…Their study showed a 154.241 μg/ml IC50 value for the anticancer activity for Vero cells, 71.24 μg/ml IC50 value for WiDr cells, and 83.18 μg/ml value for antioxidant activity (Burhan et al, 2019).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 96%
“…Ethanolic extract from mulberry stem had potent antioxidant and antimutagenic activities. Their study showed a 154.241 μg/ml IC50 value for the anticancer activity for Vero cells, 71.24 μg/ml IC50 value for WiDr cells, and 83.18 μg/ml value for antioxidant activity (Burhan et al, 2019). Guangsangon E, a novel Diels‐Alder‐adduct, isolated from M. alba leaves, was studied in CNE1 and A549 cells.…”
Section: Therapeutic Effectsmentioning
confidence: 99%
See 1 more Smart Citation